A case series of premenstrual disorders presenting to the UK's National Female Hormone Clinic - Reilly, TJ; Knox, C-L; Marsh, MS; Craig, MC (Cambridge University Press, 2022)
Aims and method We aimed to describe the clinical characteristics of female patients presenting with premenstrual disorders to a tertiary service in the UK. We conducted a retrospective case-note review of referrals to the National Female Hormone Clinic from April 2014 to August 2020. Based on clinical assessment, we determined whether the patient met criteria for premenstrual dysphoric disorder or premenstrual exacerbation of an underlying psychiatric disorder.